Changes in Posttraumatic Growth After a Virtual Contemplative Intervention During the COVID-19 Pandemic. (January 2023) - Pfeiffer, Katherine; Cunningham, Tim; Cranmer, John N.; Harrison, Timothy; Crosby, Hannah; Schroeder, Karla; Jordan, Dorothy; Coburn, Caroline
Abstract : OBJECTIVE: The aim of this study was to describe the effects of an intervention called "Compassion & Growth Workshops" on reported posttraumatic growth (PTG) using the Posttraumatic Growth Inventory–Expanded (PTGI-X). BACKGROUND: Few studies measure the impact of interventions, such as contemplative practices, on nurse PTG. METHODS: We delivered a series of three 2-hour microretreats to nurses and advanced practice nurses and measured their impact on PTG scores. Using multivariate logistic regression, we identified cofactors predictive of 25% overall improvement on the PTGI-X. RESULTS: Overall PTG increased among participants, with the greatest improvement in relating to others, new possibilities, and personal strength. Posttraumatic growth improved as workshop attendance increased; nurses providing direct patient care also benefitted the most. CONCLUSIONS: Contemplative interventions can substantively improve PTG. This may be particularly relevant for coping with COVID pandemic stress among nurses on the frontlines and for healthcare leaders seeking to strengthen psychological support within their teams and reform the workplace environment.